Tests of partnership: Transatlantic cooperation in cyber security, internet governance, and data protection - Annegret Bendiek (Stiftung Wissenschaft und Politik (SWP), 2014)
Although relations are currently being tested, the transatlantic cyber partnership continues to stand on a solid normative and institutional foundation. Both sides agree on the fundamentals of Internet regulation. Both are of the conviction that universal accessibility to the Internet is extraordinarily useful not only for democratic decision-making and free markets but also for the future of the liberal democratic order. And both sides are united also in the search for effective means to limit malicious software, to fight crime, and to secure critical infrastructure. The controversy surrounding the NSA's espionage activities exposed differences in what the United States and EU member countries consider to be the legitimate means and methods of reaching their common goals. It also revealed that they have different approaches to handling normative dissonance. Nevertheless, it certainly should not be misunderstood as an existential threat to the transatlantic partnership. Instead, transatlantic differences can and should be speedily resolved through political dialogue. Three major problem areas must be dealt with in this process: firstly the critical infrastructure protection in transatlantic cyber security, secondly the development of an inclusive multistakeholder-model in Internet governance and thirdly the adoption of the so-called umbrella agreement in data protection between the US and the EU. This Research Paper has also been published by the Transatlantic Academy and the German Marshall Fund of the United States. (SWP Research Paper)
Keywords: 320